2009
DOI: 10.1038/sj.bjc.6605048
|View full text |Cite
|
Sign up to set email alerts
|

Radical hysterectomy for FIGO stage I–IIB adenocarcinoma of the uterine cervix

Abstract: A retrospective analysis was carried out to identify risk factors for survival and relapse in patients with FIGO stage I -IIB cervical adenocarcinoma (AC), who underwent radical hysterectomy, and to compare outcome and spread pattern with those of squamous cell carcinoma (SCC). One hundred and twenty-three FIGO stage I -IIB patients with AC and 455 patients with SCC, who all underwent primary radical hysterectomy, were reviewed. Among the patients with AC, Cox model identified tumour size (95% CI: 1.35 -30.71)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 20 publications
4
71
0
4
Order By: Relevance
“…Consistently reported independent adverse prognostic factors for patients with early-stage cervical cancer after RH include higher FIGO stage, lymph node metastasis, parametrial involvement, depth of cervical stromal invasion, tumour size and LVSI (Look et al, 1996;Lai et al, 2007;Kasamatsu et al, 2009). We also found that these factors were significant in univariate analysis, although only lymph node metastasis, parametrial involvement and tumour size were significant in multivariate analysis.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Consistently reported independent adverse prognostic factors for patients with early-stage cervical cancer after RH include higher FIGO stage, lymph node metastasis, parametrial involvement, depth of cervical stromal invasion, tumour size and LVSI (Look et al, 1996;Lai et al, 2007;Kasamatsu et al, 2009). We also found that these factors were significant in univariate analysis, although only lymph node metastasis, parametrial involvement and tumour size were significant in multivariate analysis.…”
Section: Discussionmentioning
confidence: 50%
“…Although several studies reported that the time to recurrence was shorter in patients with AdCa and AdSCCa than in those with SCCa, more recent work has found no difference associated with histologic type (Look et al, 1996;Lai et al, 1999). When classified into recurrence inside and outside the pelvis, the pattern of spread and recurrence did not differ among histologic groups in some studies (Look et al, 1996;Lai et al, 1999;Grisaru et al, 2001), whereas other reports showed an association between histologic type and more frequent disseminated peritoneal spread or distant metastasis (Drescher et al, 1989;Eifel et al, 1995;Kasamatsu et al, 2009). In our series, recurrence outside the pelvis was more frequent in patients with AdCa.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The Gynecologic Oncology Group study demonstrated that there was no difference in the distribution of high-risk pathological factors (pelvic node metastasis, parametrial extension, and surgical margins) and survival between cell types, but there was shorter survival in those with adenosquamous carcinoma (Look et al, 1996). Similarly, Kasamatsu et al reported that for FIGO stage I-IIB cervical cancer patients who had radical hysterectomy, the spread pattern and prognosis were comparable between those with squamous cell carcinoma and adenocarcinoma (Kasamatsu et al, 2009). Data from the previous study by our group were in accordance with these findings (Rudtanasudjatum et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…A US study of patients from 1997 to 2003 in the SEER database found 5-year overall survivals of 32.5% for patients with SNEC, 74.3% for ADC and 64.6% for SCC (Chen et al, 2008). Some studies have reported 2.6-2.9 times higher mortality among patients with early stage ADC compared with early-stage SCC patients over 10-19 years of follow-up (Nakanishi et al, 2000;Takeda et al, 2002;Park et al, 2010;Mabuchi et al, 2012) while others have not found any significant difference in survival among patients with SCC and ADC (Shingleton et al, 1995;Lee et al, 2006;Fregnani et al, 2008;Kasamatsu et al, 2009;Narukon et al, 2010). Moreover, only few studies have included patients with SNEC.…”
Section: Introductionmentioning
confidence: 99%